2019
DOI: 10.1016/j.tplants.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin – A Developing Story

Abstract: In the past decade, tremendous advance has been made in understanding the biosynthesis, perception and signaling pathways of the plant hormone cytokinin. It also became clear that interfering with any of these steps greatly impacts all stages of growth and development. This has spurted renewed effort recently to understand how cytokinin signaling affects developmental processes. As a result, new insights on the role of cytokinin signaling and the downstream targets during e.g. shoot apical meristem, flower, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(117 citation statements)
references
References 90 publications
(110 reference statements)
1
113
0
3
Order By: Relevance
“…3 ), the only Salicaceae species with SDR precisely assembled (Zhou et al , 2020; Xue et al , 2020). Recent progress has revealed that the genes involved in cytokinin signaling play important roles in the regulation of unisexual flower development in plants (Wybouw et al , 2019; Kieber et al , 2018; Feng et al , 2020). Specifically, a Y-specific type-C cytokinin response regulator ( Shy Girl , SyGI ) was recently identified as a suppressor of carpel development and therefore is a strong candidate of sex determination in kiwifruit (Akagi et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…3 ), the only Salicaceae species with SDR precisely assembled (Zhou et al , 2020; Xue et al , 2020). Recent progress has revealed that the genes involved in cytokinin signaling play important roles in the regulation of unisexual flower development in plants (Wybouw et al , 2019; Kieber et al , 2018; Feng et al , 2020). Specifically, a Y-specific type-C cytokinin response regulator ( Shy Girl , SyGI ) was recently identified as a suppressor of carpel development and therefore is a strong candidate of sex determination in kiwifruit (Akagi et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokinin signaling pathway has emerged in recent years as a prominent candidate for regulating floral development and sex expression in plants [46, 47]. Cytokinin signaling in Arabidopsis functions as a His-Asp phosphorelay system that transduces the signal from dual function membrane-bound histidine kinases in the endoplasmic reticulum, through histidine phosphotransferases to the type B response regulators (ARR).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, disruption of this pathway at multiple stages has resulted in modified reproductive development, with cytokinin typically being implicated in enhancing development of female floral parts [46]. For example, it has recently been shown that the Type B response regulators ARR1 and ARR10 bind to the promoter region of the floral homeotic gene AGAMOUS , and down-regulation of these genes inhibits carpel regeneration in an in vitro assay [49].…”
Section: Discussionmentioning
confidence: 99%
“…The crucial cytokinin role is stimulation of cell division and differentiation, e.g. in shoot and flower development, female gametophyte development as well as vascular tissue and root meristem development and root nodule formation (Wybouw and De Rybel 2019). In plants, the active cytokinins are trans-zeatin (tZ), N6-(Δ 2 -isopentenyl)-adenine (iP), cis-zeatin (cZ), and dihydrozeatin (Haberer and Kieber 1 3 2002).…”
Section: Major Decrease Of the Cytokinin Ip In Bs Berries During The mentioning
confidence: 99%